Demonstrated Advantages and Considerations of a Beta Nucleated Polypropylene Piping System Versus a Stainless Steel Piping System - Toribio Pando, Pedro Angel (2022)
A polymer is a thermoplastic material that crystallizes in three forms: α (monoclinic), β (trigonal) and γ (orthorhombic). These forms have characteristics that provide specific physicochemical properties in the same formulation. The α crystalline form is found in higher proportion and is the most stable and simplest to produce. However, the raw material of the beta-nucleated polypropylene and PR (pressure resistant), monolayer pipes and PR fiber polypropylene pipes are processed to produce β structures in ways where it would be easier to have α crystals, since this process favors the formation of a stable, fine hexagonal crystalline structure and a homogeneous size distribution. These attributes derive in an optimization of the mechanical performance of the system, in which a mixture of these forms (α and β) will provide a very optimal thermo‑mechanical property.